Trends in mathematics learning in Ethiopia: 2012 - 2019 - Dawit T. Tiruneh; Ricardo Sabates; Caine Rolleston; John Hoddinott (College of education, Bahir Dar University, 2023)
This study examines the trends in mathematics learning for Grade 4 pupils in Ethiopia based on a longitudinal survey of 33 schools from 2012-13 to 2018-19. The study employs unique data collected both at the start and end of the General Education Quality Improvement Program - Phase II (GEQIP-II) reform targeting the same schools in six regions. The data included repeated measures of pupil learning outcomes plus child socio-economic background, teacher, and school characteristics. Despite the implementation of the GEQIP-II reform, we found that pupils' mathematics learning levels declined between 2012-13 and 2018-19. Progress in mathematics within the 2018-19 academic year improved slightly compared to 2012-13, but there is difference in magnitude of learning progress for the two periods between pupils across rural-urban locations, regional states, and family economic backgrounds. There is an overall improvement in school and teacher 'quality' between 2012 and 2019, while there is some evidence of changes in student composition between the two periods. Consistent with the GEQIP-II reform in terms of supporting access and retention, pupils in 2018-19 were more likely to have attended pre-school, less often absent from school, and less likely to have dropped out, compared to pupils in the same grade level in 2012-13. In 2018-19, pupils' caregivers are less likely to be literate, they have fewer assets at home, and they travel a relatively longer distance to school. Differences in mathematics learning levels and learning progress between disadvantaged pupils (i.e., pupils from rural areas, emerging regions, poorest socio-economic background) and their relatively advantaged counterparts are discussed in relation to the GEQIP-II educational reform.